Marketing Strategy of the Growth and Development Clinic at RSI PKU Muhammadiyah Pekajangan - Mustikasari, Linda Ayu; Agushybana, Farid; Arso, Septo Pawelas (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to identify and analyze the marketing strategies implemented by the Growth and Development Clinic at RSI PKU Muhammadiyah Pekajangan. The research employs a qualitative descriptive method, collecting data through in-depth interviews, observations, and document analysis. The findings reveal that effective marketing strategies involve a combination of digital promotion, community relations, and service quality improvement. These findings provide valuable insights for the development of marketing strategies in the healthcare sector, particularly in the context of child development clinics.